Correlating rheology and printing performance of fiber-reinforced bioinks to assess predictive modelling for biofabrication - Sonnleitner, David; Schrüfer, Stefan; Berglund, Linn; Schubert, Dirk W.; Lang, Gregor (Journal of Materials Research, 2021)
A crucial property for the evaluation of bioinks, besides biocompatibility, is printability, which is determined by resolution and shape fidelity. Recently, fiber reinforcement was used to overcome rheological limitations and introduce biomimetic structuring. This study provides a systematic approach to evaluate the printability of fiber reinforced hydrogels. Alginate and Pluronic hydrogels were blended with cellulose nanofibers (CeNF) and polycaprolactone (PCL) microfibers. SEM imaging revealed fiber-induced structural changes. Oscillatory rheological experiments showed that the addition of fiber fragments significantly altered the complex viscosity. A customized setup was utilized to determine strut spreading behavior in a real extrusion printing process. Strikingly, the data displayed excellent correlation with viscoelastic model-based predictions. CeNF increased the shape fidelity of both hydrogels, while PCL microfibers increased the viscosity but resulted in a time dependent loss of structural integrity in Pluronic. The results emphasize the need to complement shear-rheological analysis of bioinks by print-related customized analytical tools.<br
CRIS-Team Scopus Importer:2021-07-16
Keywords: 3D printing; Composite; Extrusion; Fiber; Modeling; Viscoelasticity